The open sea as the main source of methylmercury in the water column of the Gulf of Lions (Northwestern Mediterranean margin). (15th February 2017) - Cossa, Daniel; Durrieu de Madron, Xavier; Schäfer, Jörg; Lanceleur, Laurent; Guédron, Stéphane; Buscail, Roselyne; Thomas, Bastien; Castelle, Sabine; Naudin, Jean-Jacques
Abstract: Despite the ecologic and economical importance of coastal areas, the neurotoxic bioaccumulable monomethylmercury (MMHg) fluxes within the ocean margins and exchanges with the open sea remain unassessed. The aim of this paper is to address the questions of the abundance, distribution, production and exchanges of methylated mercury species (MeHgT), including MMHg and dimethylmercury (DMHg), in the waters, atmosphere and sediments of the Northwestern Mediterranean margin including the Rhône River delta, the continental shelf and its slope (Gulf of Lions) and the adjacent open sea (North Gyre). Concentrations of MeHgT ranged from <0.02 to 0.48 pmol L −1 with highest values associated with the oxygen-deficient zone of the open sea. The methylated mercury to total mercury proportion (MeHgT/HgT) increased from 2% to 4% in the Rhône River to up to 30% (averaging 18%) in the North Gyre waters, whereas, within the shelf waters, MeHgT/HgT proportions were the lowest (1–3%). We calculate that the open sea is the major source of MeHgT for the shelf waters, with an annual flux estimated at 0.68 ± 0.12 kmol a −1 (i.e., equivalent to 12% of the HgT flux). This MeHgT influx is more than 80 times the direct atmospheric deposition or the in situ net production, more than 40 times the estimated "maximum potential" annual efflux from shelf sediment, and more than 7 times that of the continental sources. In the open sea, ratios of MMHg/DMHg in waters were always <1 and minimum in the oxygen deficient zones of the water column, where MeHg concentrations are maximum. This observation supports the idea that MMHg could be a degradation product of DMHg produced from inorganic divalent Hg.